Analisis Politik Identitas Dalam Pemilhan Kepala Desa - Elpius Kalembang (Program Studi Imu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Timor, 2019)
Abstract After the 1998 reformation, Indonesia experienced significant political system changes, including the party system, the electoral system, and the relationship between the central government and regional governments. The purpose of this study is to analyze the Politics of Identity in the Election of Village Heads. The method in this research is descriptive qualitative. The focus of his research is the level of local political interest (ethnicity), the level of intensity of ethnicity issues and the level of production of ethnicity issues in the campaign process. The analysis technique in this study is the Interactive Milles and Habermans model. The results showed that in the village head election there were local political interests. Seen from the intervention and direction of the masses to choose a particular partner. The intensity of ethnicity issues in the election of Wederok Village Head is related to two things namely the nature of adat and the landlord. Ethnicity product products come from interest groups. Researchers suggest the need for political education for the community, the revitalization of Adat in accordance with ancestral habits and reconciliation between members of the Ikumuan Tribe.